From records to results: Report on the digital landscape of Kenya’s red meat value chain - Paliwal, Ambica; Ojango, Julie M.K.; Rao, E.J.O. (International Livestock Research Institute, 2025)
This report synthesizes insights captured during the red meat value chain (RMVC) digital landscape workshop in Kenya. Contributions from livestock keepers and traders, feed suppliers, policymakers, financial institutions, and county/national agencies were consolidated to assess current digital tool use, data flows, readiness levels, key constraints, and innovation opportunities.